Impacts on microbial communities in sediments by aquaculture farming during one salmon cycle - Johansen, Bjarta O.; Mikalsen, Svein-Ole; Magnussen, Eyðfinn; Patursson, Esbern J.; á Norði, Gunnvør; Djurhuus, Anni (Frontiers in Marine Science, 2024)
In recent years, the salmon farming industry has grown significantly worldwide, and in the Faroe Islands, it has become a major industry with an annual production of over 94,000 tonnes, yielding 24% of the GDP. According to environmental regulations, the ocean floor is monitored during every production cycle at all farming sites, involving macrofaunal, sensory, and chemical analyses. However, the impact of farming activity on microorganisms in the Faroe Islands remains unknown. This study aimed to assess the impact of Atlantic salmon farming on benthic microbial communities, giving a better understanding of the effects on the foundation of the benthic food web and to assess if these are more prone to environmental impact than traditional macrofaunal biomonitoring. Sediment cores were sampled along a transect from directly below the salmon cages to a background reference site. The sampling occurred prior to the release of salmon into the cages (‘before stocking’) and immediately before the salmon were harvested (‘peak biomass’). The 16S rRNA (V4-V5) gene was sequenced on an Illumina MiSeq from our sediment samples at the surface, 3 cm, and 10 cm depth. Significant shifts in microbial community composition were observed between ‘before stocking’ and ‘peak biomass’, as well as between different depth layers. Microbial diversity increased with increasing distance from the cages and was at its highest ‘before stocking’, indicating a significant impact of the salmon farming on the microbial community structure. In contrast to the regularly executed environmental monitoring, the results from this study showed an impact on the sediments by the salmon farming, underlining the powerful alternative of DNA-metabarcoding when biomonitoring an aquaculture area.